Leveraging local health system resources to address quality healthcare gaps in sub-Saharan African: lessons from the SafeCare quality improvement programme in Ghana - Robert Kaba Alhassan; Maxwell Akwasi Antwi; Gifty Sunkwa-Mills; Bonifacia Benefo Agyei; Aafke de Graaff; Tobias F Rinke de Wit; Edward Nketiah-Amponsah (BMC, 2024)
Abstract Introduction In low- and-middle-income-countries (LMICs) like Ghana, universal access to quality healthcare remains a mirage and this undermines achievement of sustainable development goal (SDG) 3. The SafeCare Quality Improvement (QI) programme is an initiative of PharmAccess Foundation, a Netherlands-based non-governmental organisation (NGO). In 2009 SafeCare QI programme was launched in Ghana to help address gaps in healthcare quality standards, leveraging existing local resources. Over 600 private and public healthcare facilities are currently enrolled in the programme and is being adopted for nation-wide rollout by government of Ghana and implementing partners. Objective This paper explored views and experiences of frontline health staff and policy makers on the SafeCare quality improvement programme in Ghana and how local resources were leveraged in its implementation. Methodology Design/setting: The evaluation was conducted in 53 private and public healthcare facilities from seven administrative regions of Ghana across the coastal, middle, and northern geopolitical belts. The regions are Ashanti (n = 12), Bono East (n = 8), Bono (n = 3), Greater Accra (n = 12), Oti (n = 4), Savannah (n = 8) and Western (n = 9). Sampling: Quota and purposive sampling techniques were used to sample the healthcare facilities in accordance with the study eligibility criteria. Total of 45 focus group discussions (FGDs) and 47 individual in-depth interviews (IDIs) were conducted among frontline staff and policy makers from government and private local partner institutions. Analysis: Group and individual interviews were audio recorded, transcribed verbatim and thematic content analysis done using Nvivo (version 12.0) software. Findings Overall, participants perceived the relevance and benefits of the SafeCare programme to be "very satisfactory" while the programme impact, rollout process and success were perceived to be "satisfactory". Quality healthcare standards were perceived to have improved in beneficiary health facilities due to participation in the SafeCare programme. Patient satisfaction, service utilisation and revenue generation in healthcare facilities were also attributed to the SafeCare programme. Proposals were made for harmonisation of existing QI assessment tools to mitigate duplications. Agreed data sharing protocols and interoperability with existing national database were also recommended to promote sustainability. Finally, low staff motivation, high workload, lack of financial and material resources were cited as potential impediments to full compliance with the SafeCare QI standards by healthcare facilities enrolled in the programme. Conclusions SafeCare QI programme has contributed to QI and adherence to patient safety standards in Ghana. Sustainability is however dependent on continuous government commitment as the programme gets adopted as a national QI programme. Overlaps in content of QI assessment tools ought to be addressed to promote efficiency without compromising quality standards. The SafeCare programme demonstrates that health systems in LMICs have the potential to attain acceptable quality healthcare standards when they take advantage of existing local resources, including private-public partnership (PPP) and peer-learning opportunities.